Be Strong or Weak: The Contribution of Parenting Style toward Parent Involvement Motivation in Accompanying Children During Learning from Home - Hanggara Budi Utomo; Veny Iswantiningtyas; Dema Yulianto (Journal of Educational, Health and Community Psychology, 2021)
The urgency of parental involvement in assisting children's learning from home is to increase children's academic success. The purpose of this study was to analyze the motivational role of parental involvement in accompanying children during learning from home in terms of parenting style. This empirical information can be used as a basis for determining parenting styles and motivation for parental involvement in accompanying children during learning from home. The participants of this study were parents totaling 282 with details of 42 people or about 15% were fathers, and 240 people or about 85% were mothers (Mean=1.85; SD=0.357). The research data was taken using a questionnaire with parental involvement motivation instruments (Katz et al., 2011) and parenting style instruments (Robinson et al., 2001). The test of hypothesis used the Doubled Regression Analysis Technique (SPSS 22). The results of this study indicate that authoritative, authoritarian, and permissive parenting styles are simultaneously effective in determining parental involvement motivation (R Square = 0.45, p < 0.01).